T-T interaction in the generation of helper cells in vitro. - Feldmann, M; Kilburn, D; Levy, J (1975)
Levy and her colleagues have reported that the antigen performic acid oxidised ferrodoxin (OFd), derived from Clostridium pasteurianum has only 2 major antigenic determinants located in the carboxyl and amino terminal regions of the molecule. They reported that cooperation between cells primed to the determinants situated at the COOH (C hapten) and at the NH2 terminus (N hapten) is necessary for the generation of a proliferative response of guinea pig lymph node cells in vitro to the whole antigen, OFd, but not for the expression of hypersensitivity reactions. Having recently described a system for the development of helper cells in vitro, the authors attempted to determine whether the T helper cell response to OFd required cooperation between two populations of T cells, in analogy with other cooperative proliferative response to OFd.